The debate on the trial of the Templars (1307 - 1314) - Burgtorf, Jochen (Ashgate, 2010)
Could alleged Templar malpractices have remained undetected for decades? / Alan Forey -- The election of the Templar master Jacques de Molay / Anthony Luttrell -- Institutional dependency upon secular and ecclesiastical patrons and the foundations of the Trial of the Templars / Nicholas Morton -- Fighting the King of France : Templars and Hospitallers in the Flemish Rebellion of 1302 / Bernard Schotte -- The monetary fluctuations in Philip IV's Kingdom of France and their relevance to the arrest of the Templars / Ignacio de la Torre -- Terror, torture, and the truth : the testimonies of the Templars revisited / Thomas Krämer -- The Templars face the inquisition : the Papal Commission and the Diocesan tribunals in France, 1308-11 / Dale R. Streeter -- Three "traitors" of the Temple : was their truth the whole truth? / David Bryson -- The trial inventories of the Templars' houses in France : select aspects / Jochen Burgtorf -- On the margins of the Templars' trial : the case of Bishop Guichard of Troyes / Alain Provost -- The involvement of the University of Paris in the trials of Marguerite Porete and the Templars, 1308-10 / Paul F. Crawford -- The trial depositions as evidence of kinship influences in the order of the Temple / Jochen G. Schenk -- The social reception of the Templar trial in early fourteenth-century France : the transmission of information / Magdalena Satora -- Reassessing the dissolution of the Templars : King Dinis and their suppression in Portugal / Clive Porro -- Icons, crosses, and the liturgical objects of Templar chapels in the crown of Aragon / Sebastián Salvadó -- The extinction of the order of the Temple in the Kingdom of Valencia and early Montesa, 1307-30 : a case of transition from universalist to territorialized military orders / Luis García-Guijarro Ramos -- King Edward II of England and the Templars / Jeffrey S. Hamilton -- The Trial of the Templars in Ireland / Helen J. Nicholson -- The Hospitallers' acquisition of the Templar lands in England / Simon Phillips -- The arrest of the Templars in Cyprus / Peter W. Edbury -- Rinaldo da Concorezzo, Archbishop of Ravenna, and the Trial of the Templars in Northern Italy / Elena Bellomo -- The Templars and their trial in Sicily / Kristjan Toomaspoeg -- The Trial of the Templars in the County of Flanders, 1307-12 / Filip Hooghe -- The commanderies of the Templars in the Polish lands and their history after the end of the order / Maria Starnawska -- Templar runaways and renegades before, during and after the trial / Christian Vogel -- Priests of the order of the Temple : what can they tell us? / Anne Gilmour-Bryson -- The assimilation of Templar properties by the order of the Hospital / Theresa M. Vann -- "The Templars are everywhere" : an examination of the myths behind Templar survival after 1307 / John Walker